Flame-retardant efficient cross-linked polyolefin cable body and preparation method thereof

By employing a method of phosphorus-nitrogen heterocyclic silane-plasma synergistic modification and the introduction of organic small molecules, the low efficiency of polyolefin materials in flame retardant modification and crosslinking processes has been solved, resulting in highly efficient flame-retardant and highly crosslinked cable materials, thereby improving the safety and stability of cables.

CN121045696APending Publication Date: 2025-12-02安徽百商百德电缆有限公司
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202511395386.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-28
Publication Date
2025-12-02

AI Technical Summary

Technical Problem

Existing polyolefin materials suffer from low flame retardant efficiency, insufficient crosslinking degree, and decreased mechanical properties during flame retardant modification and crosslinking processes, making it difficult to meet the safety and stability requirements of high-performance cables.

Method used

A polyolefin matrix modified by phosphorus-nitrogen heterocyclic silane-plasma synergistic modification was adopted, and 2,4-dihydroxy-6-methylbenzamide, an organic small molecule, was introduced. Combined with intumescent flame retardant, peroxide crosslinking agent, antioxidant, light stabilizer and lubricant, flame retardant and high-efficiency crosslinked polyolefin cable body was prepared by melt granulation and crosslinking molding process.

Benefits of technology

It significantly improves flame retardant efficiency and cross-linking degree, enhances the interfacial bonding between the matrix and functional components, improves the flame retardancy and mechanical properties of the cable body, and forms a unique technical effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121045696A_ABST
    Figure CN121045696A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of cable materials, in particular to a flame-retardant efficient cross-linked polyolefin cable body and a preparation method thereof. The cable body comprises a polyolefin matrix, 2, 4-dihydroxy-6-methyl benzamide, an intumescent flame retardant, dicumyl peroxide, an antioxidant, a light stabilizer and a lubricant, wherein the polyolefin matrix is subjected to synergistic modification by phosphorus-nitrogen heterocyclic silane-plasma. The preparation method of the polyolefin matrix synergistically modified by phosphorus-nitrogen heterocyclic silane-plasma comprises the following steps: performing grafting reaction on polyolefin resin and phosphorus-nitrogen heterocyclic silane under the action of an initiator, and performing plasma surface treatment to endow the material with dual active sites. The preparation method comprises the following steps: melting and granulating a polyolefin matrix subjected to phosphorus-nitrogen heterocyclic silane-plasma synergistic modification, small organic molecules and auxiliaries, and performing extrusion molding under a crosslinking condition to obtain a cable body. The material disclosed by the invention has comprehensive advantages in flame-retardant efficiency, crosslinking degree and mechanical property, and is suitable for manufacturing high-safety power cables.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of cable material technology, specifically to a flame-retardant, high-efficiency cross-linked polyolefin cable body and its preparation method. Background Technology

[0002] Polyolefin materials are widely used in cable insulation and sheathing layers due to their excellent electrical insulation properties, low dielectric constant, good processability, and moderate cost. However, the lack of polar functional groups in the polyolefin molecular chain results in a non-polar structure, leading to insufficient interfacial compatibility with functional components such as flame retardants and crosslinking agents. This results in low flame retardant efficiency and a slow crosslinking reaction rate, making it difficult to meet the safety and stability requirements of high-performance cables.

[0003] In terms of flame retardant modification, common methods include adding inorganic fillers such as aluminum hydroxide and magnesium hydroxide, or using intumescent flame retardants based on the ammonium polyphosphate / melamine / pentaerythritol system. These flame retardant systems exhibit poor dispersibility in polyolefin matrices, often requiring high addition levels to achieve the desired flame retardant effect. However, high addition levels can lead to problems such as decreased mechanical properties, reduced electrical insulation properties, and insufficient flexibility in the material.

[0004] Regarding crosslinking methods, common silane crosslinking requires catalytic hydrolysis and humid heat conditions, resulting in long process cycles; irradiation crosslinking relies on specialized radiation devices, leading to high equipment investment and operating costs; while peroxide crosslinking is commonly used, it suffers from insufficient crosslinking degree, poor thermo-oxidative stability, and byproduct residues. These shortcomings make it difficult for traditional crosslinked polyolefin materials to simultaneously achieve high flame retardancy and high stability.

[0005] Therefore, how to design a new method for modifying polyolefins, introduce functional structures at the molecular level that can improve the polarity and reactivity of the matrix, and combine them with novel small molecule synergistic components to improve the dispersibility and crosslinking efficiency of flame retardants has become a key problem that urgently needs to be solved in the field of cable material technology. Summary of the Invention

[0006] To overcome the problems of low flame retardant efficiency, insufficient crosslinking degree, and decreased mechanical properties of materials in the aforementioned background technologies, the present invention aims to provide a flame-retardant, high-efficiency crosslinked polyolefin cable body and its preparation method. The present invention employs a polyolefin matrix modified by phosphorus-nitrogen heterocyclic silane-plasma synergy, and introduces a simple organic small molecule, 2,4-dihydroxy-6-methylbenzamide, which has not been used in the cable field. Simultaneously, it is combined with an intumescent flame retardant, a peroxide crosslinking agent, an antioxidant, a light stabilizer, and a lubricant. The flame-retardant, high-efficiency crosslinked polyolefin cable body is prepared through melt granulation and crosslinking molding processes. Compared with existing technologies, the present invention significantly improves flame retardant efficiency, enhances the interfacial bonding between the matrix and functional components, improves the degree of crosslinking and thermal stability, and enables the cable body to possess both excellent flame retardancy and mechanical properties.

[0007] The objective of this invention can be achieved through the following technical solutions:

[0008] A flame-retardant, high-efficiency cross-linked polyolefin cable body comprises the following raw materials in parts by weight: 50-80 parts of polyolefin matrix synergistically modified with phosphorus-nitrogen heterocyclic silane-plasma; 5-20 parts of 2,4-dihydroxy-6-methylbenzamide; 10-25 parts of intumescent flame retardant; 1-3 parts of dicumyl peroxide; 0.3-1.0 parts of antioxidant 1010; 0.2-0.8 parts of light stabilizer; and 0.5-2 parts of lubricant.

[0009] Optionally, the polyolefin matrix modified by phosphorus-nitrogen heterocyclic silane-plasma synergistic modification comprises the following raw materials in parts by weight: 80-95 parts of polyolefin resin; 3-10 parts of phosphorus-nitrogen heterocyclic silane; 1-5 parts of coupling agent; and 50-100 parts of polar solvent.

[0010] Optionally, the method for preparing a polyolefin matrix modified by phosphorus-nitrogen heterocyclic silane-plasma synergistic modification includes the following steps:

[0011] (1) Mix polyolefin resin, phosphorus nitrogen heterocyclic silane, coupling agent and polar solvent, and carry out grafting reaction to obtain grafted product;

[0012] (2) The grafted product is separated, washed and dried to obtain a polyolefin solid product;

[0013] (3) The solid polyolefin product is subjected to plasma surface treatment to obtain a polyolefin matrix modified by phosphorus nitrogen heterocyclic silane-plasma synergistic modification.

[0014] Optionally, the grafting reaction conditions in step (1) are to react at 120-150°C for 2-4 hours in the presence of an initiator; the power of the plasma surface treatment in step (3) is 50-200W, and the treatment time is 2-10 minutes.

[0015] Optionally, 2,4-dihydroxy-6-methylbenzamide is a small organic molecule of the benzamide class containing two hydroxyl groups and one amide group.

[0016] Optionally, the intumescent flame retardant is a mixture of ammonium polyphosphate and melamine in a mass ratio of 2:1; the antioxidant 1010 is a mixture of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenylpropionic acid)] and tris(2,4-di-tert-butylphenyl) phosphite in a mass ratio of 1:1; the light stabilizer is a mixture of hindered amine light stabilizer 770 and benzophenone-based ultraviolet absorber UV-531 in a mass ratio of 1:1; and the lubricant is a mixture of calcium stearate and liquid paraffin in a mass ratio of 1:1.

[0017] Optionally, a method for preparing a flame-retardant, high-efficiency cross-linked polyolefin cable body includes the following steps:

[0018] S1, add the polyolefin matrix modified by phosphorus nitrogen heterocyclic silane-plasma synergistic modification, 2,4-dihydroxy-6-methylbenzamide, intumescent flame retardant, dicumyl peroxide, antioxidant 1010, light stabilizer and lubricant into a high-speed mixer and mix evenly to obtain a mixture;

[0019] S2, the mixture is fed into a twin-screw extruder, extruded and pelletized in a heated and molten state to obtain cable body premixed granules;

[0020] S3, the premixed granules of the cable body are extruded under cross-linking conditions to obtain a flame-retardant and high-efficiency cross-linked polyolefin cable body.

[0021] Optionally, the melt granulation temperature in step S2 is 160–180°C, and the screw speed is 100–200 rpm.

[0022] Optionally, the cross-linking molding temperature in step S3 is 170–190°C, the cross-linking time is 15–30 minutes, and the gel content of the resulting cable body is 80%–90%.

[0023] The beneficial effects of this invention are:

[0024] This invention employs a phosphorus-nitrogen heterocyclic silane-plasma synergistic modification of the polyolefin matrix, simultaneously introducing phosphorus-nitrogen heterocyclic structures and surface-active groups at the molecular level. This significantly enhances the matrix's polarity and reactivity, thereby improving its interaction efficiency with flame retardants and crosslinking agents. The 2,4-dihydroxy-6-methylbenzamide introduced in this invention, a small organic molecule not previously used in the cable industry, can form a unique molecular interaction interface with the modified polyolefin, significantly improving the dispersion of the flame-retardant component in the system and providing additional intermolecular binding sites during crosslinking. Through these two innovative design aspects, this invention achieves a dual improvement in flame-retardant efficiency and crosslinking degree, resulting in a unique technical effect distinct from existing polyolefin cable materials. Attached Figure Description

[0025] The invention will now be further described with reference to the accompanying drawings.

[0026] Figure 1 A bar chart comparing the limiting oxygen index results of samples with different ratios;

[0027] Figure 2 A bar chart comparing the gel content results of samples with different ratios;

[0028] Figure 3 A bar chart comparing the tensile strength results of samples with different proportions;

[0029] Figure 4 A bar chart comparing the fracture elongation results of different samples. Detailed Implementation

[0030] The present invention will be further described below with reference to specific embodiments. However, the present invention is not limited to the following embodiments. Equivalent adjustments made without departing from the spirit and essence of the present invention should also be considered to fall within the protection scope of the present invention.

[0031] Example 1

[0032] The purpose of this embodiment is to verify the effect of the polyolefin matrix after phosphorus-nitrogen heterocyclic silane-plasma synergistic modification on the dispersibility and crosslinking efficiency of flame retardants in the system.

[0033] S1, 90 parts of polyolefin resin, 5 parts of phosphorus-nitrogen heterocyclic silane, 2 parts of coupling agent and 80 parts of polar solvent were added to a reaction vessel, and 0.5 parts of dicumyl peroxide were added as an initiator. The mixture was heated to 130°C under nitrogen protection and stirred for 3 hours. After the reaction was completed, the product was precipitated in methanol, filtered and washed three times with deionized water, and vacuum dried for 12 hours to obtain the grafted product. The grafted product was placed in a plasma reaction chamber and treated at 100W power for 5 minutes to obtain a polyolefin matrix modified by phosphorus-nitrogen heterocyclic silane-plasma synergistic modification.

[0034] S2, 60 parts of polyolefin matrix modified by phosphorus nitrogen heterocyclic silane-plasma synergistic modification, 10 parts of 2,4-dihydroxy-6-methylbenzamide, 15 parts of intumescent flame retardant, 2 parts of dicumyl peroxide, 0.5 parts of antioxidant 1010, 0.5 parts of light stabilizer, and 1 part of lubricant are added to a high-speed mixer and mixed at 80°C for 10 minutes; the mixture is fed into a twin-screw extruder, melt-extruded at 170°C and pelletized to obtain cable body premixed granules;

[0035] S3. The premixed granules are fed into the cable extruder and cross-linked at 180°C for 20 minutes to obtain the flame-retardant high-efficiency cross-linked polyolefin cable body, with a gel content of 82%.

[0036] Example 2

[0037] The purpose of this embodiment is to investigate the effect of increasing the content of 2,4-dihydroxy-6-methylbenzamide in the system on crosslinking efficiency and flame retardant properties.

[0038] S1, take 85 parts of polyolefin resin, 6 parts of phosphorus-nitrogen heterocyclic silane, 3 parts of coupling agent and 90 parts of polar solvent, add 0.6 parts of dicumyl peroxide as initiator, stir and react at 135℃ for 2.5 hours; the resulting reactant is precipitated with methanol, washed three times with deionized water and vacuum dried to obtain the grafted product; then it is treated with plasma at 150W for 6 minutes to obtain the polyolefin matrix synergistically modified by phosphorus-nitrogen heterocyclic silane-plasma.

[0039] S2, 55 parts of polyolefin matrix modified by phosphorus nitrogen heterocyclic silane-plasma synergistic, 15 parts of 2,4-dihydroxy-6-methylbenzamide, 18 parts of intumescent flame retardant, 2 parts of dicumyl peroxide, 0.6 parts of antioxidant 1010, 0.4 parts of light stabilizer, and 1 part of lubricant are mixed and stirred at 90°C for 8 minutes in a high-speed mixer; then fed into a twin-screw extruder and melt-extruded and granulated at 175°C to obtain cable body premixed granules.

[0040] S3, the premixed granules are extruded in a cross-linking molding machine at 185°C and held for 25 minutes to obtain the flame-retardant high-efficiency cross-linked polyolefin cable body, and the gel content is measured to be 85%.

[0041] Example 3

[0042] The purpose of this embodiment is to verify the changes in the gel content and molding quality of the cable body under the adjustment of granulation and crosslinking conditions.

[0043] S1, take 88 parts of polyolefin resin, 7 parts of phosphorus-nitrogen heterocyclic silane, 2 parts of coupling agent and 95 parts of polar solvent, add 0.7 parts of dicumyl peroxide as initiator, and react at 140℃ for 3 hours; after the obtained graft product is precipitated with methanol, washed and dried, it is treated in a plasma chamber at 200W power for 8 minutes to obtain a polyolefin matrix modified by phosphorus-nitrogen heterocyclic silane-plasma synergistic modification.

[0044] S2, 65 parts of polyolefin matrix modified by phosphorus-nitrogen heterocyclic silane-plasma synergistic modification, 8 parts of 2,4-dihydroxy-6-methylbenzamide, 20 parts of intumescent flame retardant, 3 parts of dicumyl peroxide, 0.8 parts of antioxidant 10100, 0.6 parts of light stabilizer, and 1.5 parts of lubricant are added to a high-speed mixer and stirred at 100°C for 12 minutes; then melt-extruded in a twin-screw extruder at 180°C and pelletized to obtain premixed granules;

[0045] S3, the premixed particles were cross-linked and extruded at 190°C and held for 30 minutes to obtain the flame-retardant high-efficiency cross-linked polyolefin cable body, and the gel content was measured to be 89%.

[0046] Example 4

[0047] The purpose of this embodiment is to investigate the effect of using the upper limit ratio of each major component on flame retardant performance and crosslinking efficiency.

[0048] S1, take 95 parts of polyolefin resin, 10 parts of phosphorus-nitrogen heterocyclic silane, 5 parts of coupling agent and 100 parts of polar solvent, add 1 part of dicumyl peroxide as initiator, and react at 150°C for 3 hours under nitrogen protection; after the reactants are precipitated with methanol, washed and dried, they are treated in a plasma chamber at 200W power for 10 minutes to obtain a polyolefin matrix modified by phosphorus-nitrogen heterocyclic silane-plasma synergistic modification.

[0049] S2, 80 parts of polyolefin matrix modified by phosphorus nitrogen heterocyclic silane-plasma synergistic method, 20 parts of 2,4-dihydroxy-6-methylbenzamide, 25 parts of intumescent flame retardant, 3 parts of dicumyl peroxide, 1.0 parts of antioxidant, 0.8 parts of light stabilizer, and 2 parts of lubricant are mixed and stirred at 100°C for 10 minutes in a high-speed mixer; the mixture is then melt-granulated at 180°C in a twin-screw extruder to obtain cable body premixed granules;

[0050] S3, the premixed particles are cross-linked and extruded at 190°C and held for 30 minutes to obtain a flame-retardant, high-efficiency cross-linked polyolefin cable body with a gel content of approximately 90%.

[0051] Example 5

[0052] The purpose of this embodiment is to verify the overall balance performance of the system when each component is in an intermediate ratio.

[0053] S1, take 90 parts of polyolefin resin, 6 parts of phosphorus-nitrogen heterocyclic silane, 3 parts of coupling agent and 75 parts of polar solvent, add 0.6 parts of dicumyl peroxide as initiator, and react at 135℃ for 3 hours; after the product is precipitated with methanol, washed and dried, it is treated in a plasma chamber at 120W power for 6 minutes to obtain a polyolefin matrix modified by phosphorus-nitrogen heterocyclic silane-plasma synergistic modification.

[0054] S2, 65 parts of polyolefin matrix modified by phosphorus nitrogen heterocyclic silane-plasma synergistic method, 12 parts of 2,4-dihydroxy-6-methylbenzamide, 18 parts of intumescent flame retardant, 2 parts of dicumyl peroxide, 0.6 parts of antioxidant 1010, 0.5 parts of light stabilizer, and 1 part of lubricant are mixed and stirred at 90°C for 8 minutes in a high-speed mixer; the mixture is fed into a twin-screw extruder and melt-extruded and granulated at 175°C to obtain cable body premixed granules;

[0055] S3, the premixed particles are cross-linked and extruded at 180°C and held for 20 minutes to obtain the flame-retardant high-efficiency cross-linked polyolefin cable body with a gel content of about 85%.

[0056] Example 6

[0057] The purpose of this embodiment is to investigate the effects of each component on flame retardant properties and crosslinking properties at low ratios.

[0058] S1, take 80 parts of polyolefin resin, 3 parts of phosphorus-nitrogen heterocyclic silane, 1 part of coupling agent and 50 parts of polar solvent, add 0.3 parts of dicumyl peroxide as initiator, and react at 120℃ for 2 hours; after the reactants are precipitated with methanol, washed and dried, they are treated in a plasma chamber at 50W power for 5 minutes to obtain a polyolefin matrix modified by phosphorus-nitrogen heterocyclic silane-plasma synergistic modification.

[0059] S2, 50 parts of polyolefin matrix modified by phosphorus nitrogen heterocyclic silane-plasma synergistic process, 5 parts of 2,4-dihydroxy-6-methylbenzamide, 10 parts of intumescent flame retardant, 1 part of dicumyl peroxide, 0.3 parts of antioxidant 1010, 0.2 parts of light stabilizer, and 0.5 parts of lubricant are mixed and stirred at 80°C for 10 minutes in a high-speed mixer; the mixture is fed into a twin-screw extruder and melt-granulated at 160°C to obtain cable body premixed granules;

[0060] S3, the premixed particles are cross-linked and extruded at 170°C and held for 15 minutes to obtain the flame-retardant high-efficiency cross-linked polyolefin cable body with a gel content of about 80%.

[0061] Comparative Example 1

[0062] The purpose of this comparative example is to verify the effect of the system on the dispersibility and crosslinking properties of the flame retardant when only phosphorus-nitrogen heterocyclic grafting is used and no plasma treatment is performed.

[0063] S1, take 90 parts of polyolefin resin, 6 parts of phosphorus-nitrogen heterocyclic silane, 3 parts of coupling agent and 75 parts of polar solvent, add 0.6 parts of dicumyl peroxide as initiator, and react at 135℃ for 3 hours; the obtained product is used directly after methanol precipitation, washing and drying, without plasma treatment, to obtain a polyolefin matrix grafted with a single phosphorus-nitrogen heterocyclic silane.

[0064] S2, 65 parts of the obtained polyolefin matrix, 12 parts of 2,4-dihydroxy-6-methylbenzamide, 18 parts of intumescent flame retardant, 2 parts of dicumyl peroxide, 0.6 parts of antioxidant, 0.5 parts of light stabilizer, and 1 part of lubricant are mixed and stirred at 90°C for 8 minutes in a high-speed mixer; the mixture is fed into a twin-screw extruder and melt-extruded and granulated at 175°C to obtain premixed granules;

[0065] S3, the premixed particles are cross-linked and extruded at 180°C and held for 20 minutes to obtain the flame-retardant cross-linked polyolefin cable body with a gel content of about 78%.

[0066] Comparative Example 2

[0067] The purpose of this comparative example is to verify the effect of the system on the dispersibility and crosslinking properties of the flame retardant when only plasma treatment is used and no phosphorus-nitrogen heterocyclic grafting is introduced.

[0068] S1, Take 90 parts of polyolefin resin and treat it directly in a plasma chamber at a power of 120W for 6 minutes to obtain a single plasma-modified polyolefin matrix;

[0069] S2, 65 parts of the obtained polyolefin matrix, 12 parts of 2,4-dihydroxy-6-methylbenzamide, 18 parts of intumescent flame retardant, 2 parts of dicumyl peroxide, 0.6 parts of antioxidant, 0.5 parts of light stabilizer, and 1 part of lubricant are mixed and stirred at 90°C for 8 minutes in a high-speed mixer; the mixture is fed into a twin-screw extruder and melt-extruded and granulated at 175°C to obtain premixed granules;

[0070] S3, the premixed particles are cross-linked and extruded at 180°C and held for 20 minutes to obtain the flame-retardant cross-linked polyolefin cable body with a gel content of about 76%.

[0071] Comparative Example 3

[0072] The purpose of this comparative example is to verify the changes in the flame retardant and crosslinking properties of the system without the introduction of the small organic molecule 2,4-dihydroxy-6-methylbenzamide.

[0073] S1, take 90 parts of polyolefin resin, 6 parts of phosphorus-nitrogen heterocyclic silane, 3 parts of coupling agent and 75 parts of polar solvent, add 0.6 parts of dicumyl peroxide as initiator, and react at 135℃ for 3 hours; after the product is precipitated with methanol, washed and dried, it is treated in a plasma chamber at 120W power for 6 minutes to obtain a polyolefin matrix modified by phosphorus-nitrogen heterocyclic silane-plasma synergistic modification.

[0074] S2, 65 parts of polyolefin matrix modified by phosphorus nitrogen heterocyclic silane-plasma synergistic, 18 parts of intumescent flame retardant, 2 parts of dicumyl peroxide, 0.6 parts of antioxidant 1010, 0.5 parts of light stabilizer, and 1 part of lubricant are mixed and stirred at 90°C for 8 minutes in a high-speed mixer; the mixture is fed into a twin-screw extruder and melt-extruded and granulated at 175°C to obtain premixed granules;

[0075] S3, the premixed particles are cross-linked and extruded at 180°C and held for 20 minutes to obtain the flame-retardant cross-linked polyolefin cable body with a gel content of about 74%.

[0076] Performance testing

[0077] 1. Limiting Oxygen Index Test

[0078] According to GB / T2406.2-2009 standard, the prepared cable body sample was cut into strips of 100mm×10mm×3mm, ignited in an oxygen-nitrogen mixed gas flow, and the oxygen concentration was gradually adjusted. The lowest oxygen concentration at which the sample could just sustain combustion for 3 minutes was recorded as the limiting oxygen index. The higher the limiting oxygen index, the better the flame retardant performance of the material.

[0079] 2. Vertical Burning Test

[0080] The sample was processed into a strip measuring 125mm × 13mm × 3mm and tested in a UL-94 vertical burner. The ignition time was 10 seconds. After removing the flame, the burning time was recorded, and the sample was ignited a second time. Based on indicators such as flame extinguishing time and whether the dripping material ignited cotton, the sample was rated as V-0, V-1, or V-2.

[0081] 3. Gel content test

[0082] Approximately 0.5g of cable body sample was placed in a steel mesh bag and refluxed in xylene at 135℃ for 24 hours. The sample was then removed, cooled, dried, and weighed. The mass difference before and after swelling was calculated to determine the gel content (%). This value reflects the degree of cross-linking; a higher degree of cross-linking corresponds to better thermal stability and electrical resistance.

[0083] 4. Thermogravimetric analysis test

[0084] Using a thermogravimetric analyzer, under a nitrogen atmosphere, the temperature was increased from 30℃ to 800℃ at a heating rate of 10℃ / min. The temperatures at which the sample underwent 5% and 50% thermal weight loss (T5%, T2%) were recorded. 50 This method is used to evaluate the thermal stability of the cable body; the higher the initial decomposition temperature, the better the heat resistance.

[0085] 5. Tensile property test

[0086] According to GB / T1040.2-2006 standard, the samples were prepared into standard dumbbell-shaped specimens and tested on an electronic tensile testing machine at a tensile speed of 50 mm / min to obtain tensile strength and elongation at break. This was used to compare the differences in mechanical properties between different embodiments and comparative examples.

[0087] Table 1 Comparison of Performance Test Results

[0088]

[0089] Comprehensive test results show that Examples 1-6 are significantly superior to the comparative examples in terms of flame retardancy, crosslinking degree, thermal stability, and mechanical properties. Example 5 exhibits the best performance, balancing flame retardancy efficiency, thermal stability, and mechanical properties, demonstrating the comprehensive advantages of the formulation and process of this invention. Compared to the comparative examples, this invention achieves an overall performance improvement through phosphorus-nitrogen heterocyclic silane-plasma synergistic modification and the introduction of small organic molecules, verifying the effectiveness of the inventive technical solution.

[0090] In terms of basic performance comparison, Example 1 had an oxygen index of 30%, a gel content of 82%, a thermal decomposition temperature of 295 / 460℃, a tensile strength of 17.5 MPa, and an elongation at break of 260%. Compared with Comparative Example 1's 24%, 78%, 275 / 430℃, 14.5 MPa, and 210%, the overall performance was significantly improved, indicating that synergistic modification has a significant effect on improving flame retardancy and crosslinking degree.

[0091] Regarding the role of small organic molecules, in Example 2, the amount of 2,4-dihydroxy-6-methylbenzamide was increased, the oxygen index rose to 32%, the gel content was 85%, and the thermal decomposition temperature reached 300 / 470℃, which is a further improvement compared to Example 1. This demonstrates that the small organic molecule plays a key role in improving the compatibility between the matrix and the flame retardant and enhancing the crosslinking efficiency.

[0092] Regarding process optimization, Example 3 employed higher granulation and crosslinking conditions, increasing the gel content to 89%, achieving thermal decomposition temperatures of 310 / 480℃, and an oxygen index of 34%, further enhancing performance. Example 4 used the upper limit ratio in its formulation, resulting in even higher indicators, with an oxygen index of 35%, a gel content of 90%, and thermal decomposition temperatures of 315 / 485℃, demonstrating excellent flame retardancy and thermal stability under high formulation ratios.

[0093] In terms of overall performance balance, Example 5 showed the best performance, with an oxygen index of 36%, a gel content of 85%, a thermal decomposition temperature of 320 / 490℃, a tensile strength of 18.0 MPa, and an elongation at break of 270%. It balanced flame retardancy, thermal stability, and mechanical properties, indicating that the intermediate formulation can achieve the best balance between performance and process cost. Example 6, as the lower limit ratio sample, had slightly lower performance, with an oxygen index of 28% and a gel content of 80%, but it was still better than all comparative examples, indicating that even at lower dosages, the synergistic modification system still has good performance advantages.

[0094] The comparative samples showed generally low performance. Comparative Examples 2 and 3 had oxygen indices of 23% and 22%, respectively, gel contents of 76% and 74%, thermal decomposition temperatures of only 270 / 420℃ and 265 / 415℃, tensile strength of less than 14.5 MPa, and elongation at break around 200%, significantly lower than the examples. The results indicate that neither phosphorus-nitrogen heterocyclic grafting nor plasma modification alone is sufficient to improve performance; rather, the removal of small organic molecules has a more significant impact.

[0095] In summary, the synergistic modification of phosphorus-nitrogen heterocyclic silanes by plasma and the introduction of small organic molecules have a synergistic effect on flame retardancy, crosslinking degree, thermal stability and mechanical properties, which is the core innovation of the material of this invention with excellent comprehensive performance.

Claims

1. A flame-retardant, high-efficiency cross-linked polyolefin cable body, characterized in that, The raw materials include the following parts by weight: 50-80 parts of polyolefin matrix modified by phosphorus-nitrogen heterocyclic silane-plasma synergistic modification; 5-20 parts of 2,4-dihydroxy-6-methylbenzamide; 10-25 parts of intumescent flame retardant; 1-3 parts of dicumyl peroxide; 0.3-1.0 parts of antioxidant 1010; 0.2-0.8 parts of light stabilizer; and 0.5-2 parts of lubricant.

2. The flame-retardant, high-efficiency cross-linked polyolefin cable body according to claim 1, characterized in that, The polyolefin matrix modified by phosphorus-nitrogen heterocyclic silane-plasma synergistic modification comprises the following raw materials in parts by weight: 80-95 parts of polyolefin resin; 3-10 parts of phosphorus-nitrogen heterocyclic silane; 1-5 parts of coupling agent; and 50-100 parts of polar solvent.

3. The flame-retardant high-efficiency cross-linked polyolefin cable body according to any one of claims 1 or 2, characterized in that, The method for preparing the polyolefin matrix modified by phosphorus-nitrogen heterocyclic silane-plasma synergistic modification includes the following steps: (1) Mix polyolefin resin, phosphorus nitrogen heterocyclic silane, coupling agent and polar solvent, and carry out grafting reaction to obtain grafted product; (2) The grafted product is separated, washed and dried to obtain a polyolefin solid product; (3) The solid polyolefin product is subjected to plasma surface treatment to obtain a polyolefin matrix modified by phosphorus nitrogen heterocyclic silane-plasma synergistic modification.

4. The flame-retardant, high-efficiency cross-linked polyolefin cable body according to claim 3, characterized in that, The grafting reaction conditions in step (1) are: reaction at 120-150°C for 2-4 hours in the presence of an initiator; the plasma surface treatment power in step (3) is 50-200W, and the treatment time is 2-10 minutes.

5. The flame-retardant, high-efficiency cross-linked polyolefin cable body according to claim 1, characterized in that, The 2,4-dihydroxy-6-methylbenzamide is a small organic molecule of the benzamide class containing two hydroxyl groups and one amide group.

6. The flame-retardant, high-efficiency cross-linked polyolefin cable body according to claim 1, characterized in that, The intumescent flame retardant is a mixture of ammonium polyphosphate and melamine in a mass ratio of 2:1; the antioxidant 1010 is a mixture of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenylpropionic acid)] and tris(2,4-di-tert-butylphenyl) phosphite in a mass ratio of 1:1; the light stabilizer is a mixture of hindered amine light stabilizer 770 and benzophenone-based ultraviolet absorber UV-531 in a mass ratio of 1:1; and the lubricant is a mixture of calcium stearate and liquid paraffin in a mass ratio of 1:

1.

7. A method for preparing a flame-retardant, high-efficiency cross-linked polyolefin cable body, wherein the flame-retardant, high-efficiency cross-linked polyolefin cable body is as described in any one of claims 1 to 6, characterized in that, Includes the following steps: S1, add the polyolefin matrix modified by phosphorus nitrogen heterocyclic silane-plasma synergistic modification, 2,4-dihydroxy-6-methylbenzamide, intumescent flame retardant, dicumyl peroxide, antioxidant 1010, light stabilizer and lubricant into a high-speed mixer and mix evenly to obtain a mixture; S2, the mixture is fed into a twin-screw extruder, extruded and pelletized in a heated and molten state to obtain cable body premixed granules; S3, the premixed granules of the cable body are extruded under cross-linking conditions to obtain a flame-retardant and high-efficiency cross-linked polyolefin cable body.

8. The method for preparing a flame-retardant, high-efficiency cross-linked polyolefin cable body according to claim 7, characterized in that, The melting and granulation temperature in step S2 is 160–180°C, and the screw speed is 100–200 rpm.

9. The method for preparing a flame-retardant, high-efficiency cross-linked polyolefin cable body according to claim 7, characterized in that, The cross-linking molding temperature in step S3 is 170-190°C, the cross-linking time is 15-30 minutes, and the gel content of the resulting cable body is 80%-90%.

Citation Information

Cited By

  • Phenol derivative with multi-target neuroprotective activity, production strain and application

    CN121913946A

  • Flame-retardant reinforced polypropylene composite material and preparation method thereof

    CN122080563A